An audience of one : drive superior results by making the radical shift from mass marketing to one-to-one marketing - Turner, Jamie, 1961-; Moxley, Chuck (McGraw Hill, 2021)
"The breakthrough marketing strategy today's leading companies are using to change consumer behavior and drive revenue to the bottom line Walmart, United Airlines, Jeep, and many other top companies are using the breakthrough strategy-one-to-one marketing-with amazing results, and now you can, too. An Audience of One walks you through the process of leveraging all the customer data you have at your disposal to generate and hold meaningful conversations with customers on an individual basis-all while fully respecting their privacy. Written by two of today's most renowned marketing minds, this groundbreaking guide teaches you: Key concepts of one-to-one marketing How today's leading brands are leveraging one-to-one marketing to drive growth The important role of privacy in a one-to-one marketing campaign How to use one-to-one marketing ethically and properly How to address common consumer fears and concerns about privacy How to calculate the return-on-investment of a one-to-one marketing campaign How to create an Identity Graph which predicts consumer behavior Why the traditional sales funnel no longer works-and what to replace it with Surprising insights about the customer journey and how it can be leveraged to grow sales and revenues How to create consumer profiles without invading your customers' privacy As a marketing professional, you enjoy access to a remarkable amount of data about each and every customer. An Audience of One provides the tools and techniques to get everything you can from this data, in an ethical way that benefits both you and your customers"--